Pengaruh Variasi Filter Bertingkat dan Bukaan Katup Terhadap Kinerja Gasifikasi Tipe Updraft Berbahan Pelet Kayu - Suwandono, Purbo; Prakoso, Yogi Iman; Soebiyakto, Gatot; Finahari, Nurida (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Globalization is something that we cannot avoid. Even though globalization is a good thing, there are several bad things caused by globalization. Such as population growth and increasing energy use. Excessive energy use can cause air pollution, depletion of the ozone layer, and depletion of fossil energy reserves. Therefore, it is necessary to use renewable energy from materials that we can easily get such as biomass. Utilization of biomass as energy can be converted using the gasification process. This process will produce combustible gas containing CO, H2, and CH4. This research uses several variations in air flow rate which will influence the combustion time, temperature in the reactor, and gas composition. As well as the use of various filters made from corn cobs, coconut fibers and sponges which affect the gas composition and gasification efficiency